Enhancing Early Childhood Literacy through Collaborative Learning: A Case Study in Non-Formal Education at biMBA AIUEO Jember - Hasan, Fuad; Aditya, Mohammad Arif; Faiqotul Himmah, Irliana (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Indonesia faces critical early literacy challenges, with 55% of children unable to read simple text by age 10, highlighting the need for innovative pedagogical interventions, particularly in non-formal education sectors. This qualitative case study explores the implementation and effectiveness of an integrated collaborative learning framework that combines fun learning, small-step systems, and individualized approaches to enhance early childhood literacy at biMBA AIUEO Jember, a non-formal education center. Data were collected from 15 participants (a unit head, two motivators, three parents, and nine children aged 3–6) through semi-structured interviews, systematic classroom observation over three months, and document analysis. Data were analyzed using Miles and Huberman’s (1994) interactive model with thematic coding and member checking for validity. Findings reveal four major themes: structured progression through individualized learning levels enhanced literacy acquisition; play-based engagement sustained motivation across developmental variations; adaptive facilitation addressed diverse learning needs within resource constraints; and measurable literacy growth was evident in writing complexity and reading fluency despite individual differences. The integrated framework proved effective in supporting literacy development under limited-resource conditions, though implementation challenges emerged, including uneven learner progress, limited facilitator capacity, and material scarcity. These findings underscore the global relevance of adapting collaborative learning frameworks to strengthen early literacy in resource-constrained, non-formal settings. The study extends collaborative learning theory through the concept of constrained collaboration, demonstrating that meaningful literacy growth can occur when pedagogical models are contextually grounded rather than imported from affluent systems. However, as a single-site and short-term case study, the findings have limited generalizability. Future research should employ mixed methods and longitudinal designs across diverse contexts to measure long-term literacy outcomes and scalability. Ultimately, improving early literacy in marginalized communities requires creative adaptation to local realities, affirming that quality learning can thrive even within material constraints through committed, context-responsive facilitation.